Identification of a Stelar-Localized Transport Protein That Facilitates Root-to-Shoot Transfer of Chloride in Arabidopsis . Issue 2 (11th December 2015) - Li, Bo; Byrt, Caitlin; Qiu, Jiaen; Baumann, Ute; Hrmova, Maria; Evrard, Aurelie; Johnson, Alexander A.T.; Birnbaum, Kenneth D.; Mayo, Gwenda M.; Jha, Deepa; Henderson, Sam W.; Tester, Mark; et al.
Abstract : Identification and functional analysis of a gene encoding a Cl – transporter responsible for loading Cl – into root xylem. Abstract: Under saline conditions, higher plants restrict the accumulation of chloride ions (Cl – ) in the shoot by regulating their transfer from the root symplast into the xylem-associated apoplast. To identify molecular mechanisms underpinning this phenomenon, we undertook a transcriptional screen of salt stressed Arabidopsis ( Arabidopsis thaliana ) roots. Microarrays, quantitative RT-PCR, and promoter-GUS fusions identified a candidate gene involved in Cl – xylem loading from the Nitrate transporter 1/Peptide Transporter family ( NPF2.4 ). This gene was highly expressed in the root stele compared to the cortex, and its expression decreased after exposure to NaCl or abscisic acid. NPF2.4 fused to fluorescent proteins, expressed either transiently or stably, was targeted to the plasma membrane. Electrophysiological analysis of NPF2.4 in Xenopus laevis oocytes suggested that NPF2.4 catalyzed passive Cl – efflux out of cells and was much less permeable to NO3   − . Shoot Cl – accumulation was decreased following NPF2.4 artificial microRNA knockdown, whereas it was increased by overexpression of NPF2.4 . Taken together, these results suggest that NPF2.4 is involved in long-distance transport of Cl – in plants, playing a role in the loading and the regulation of Cl – loading into the xylem of Arabidopsis roots during salinity stress.